2005
DOI: 10.1111/j.1740-0929.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Proportions of melanocyte stimulating hormone‐immunoreactive cells in the adenohypophysis of Silky fowl and hyperpigmentation‐free cockerels

Abstract: Alpha‐melanocyte stimulating hormone (α‐MSH) is one of the main regulators for melanocytes, and the adenohypophysis is one of the major tissues for the synthesis of this hormone. The Silky fowl is a characteristic breed of chicken with hyperpigmentation throughout the body. The involvement of the adenohypophysis in the hyperpigmentation of this breed is not known. In the present study, the proportion of melanocyte stimulating hormone‐immunopositive cells (MSH cells) in the adenohypophysis was immunocytochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, the regulatory effects of α-MSH and MC1R on melanin synthesis in avian species, and the mechanisms involved, are still poorly understood. Nishimura et al found that the number of α-MSH secreting cells in the anterior pituitary of silky fowl was significantly higher than common chickens with either low, or no melanin deposition, suggesting that α-MSH was closely related to deposition of melanin in the tissues [11]. Takeuchi et al cloned the MC1R gene, located on chromosome 11, for α-MSH (melanocyte-stimulating hormone) receptor from chickens for the first time in 1996 [12].…”
mentioning
confidence: 99%
“…However, the regulatory effects of α-MSH and MC1R on melanin synthesis in avian species, and the mechanisms involved, are still poorly understood. Nishimura et al found that the number of α-MSH secreting cells in the anterior pituitary of silky fowl was significantly higher than common chickens with either low, or no melanin deposition, suggesting that α-MSH was closely related to deposition of melanin in the tissues [11]. Takeuchi et al cloned the MC1R gene, located on chromosome 11, for α-MSH (melanocyte-stimulating hormone) receptor from chickens for the first time in 1996 [12].…”
mentioning
confidence: 99%